Republic of Kosovo : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Kosovo. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Republic of Kosovo's Request for Purchase Under the Rapid Financing Instrument (RFI). The coronavirus disease 2019 (COVID-19) pandemic and the associated containment measures have severely weakened Kosovo's economic outlook. The economy is expected to contract by 5 percent in 2020 as tourism receipts, remittances, exports of goods, and foreign direct investments will decrease due to travel restrictions and the effect of COVID-19 in trading partners and remittance-originating countries. The deteriorated economic outlook is expected to result in external and fiscal financing gaps. The RFI provides rapid and low-access financial assistance to member countries facing an urgent balance of payments need, without the need for a full-fledged economic program or reviews. It can provide support to meet a broad range of urgent needs, including those arising from commodity price shocks, natural disasters, conflict and post-conflict situations. Financial assistance under the RFI is provided in the form of outright purchases.